Analisis Kegagalan Material Aluminium 5052 sebagai Aplikasi Bahan Lambung Kapal Terhadap Pengaruh Salinitas Air Laut - Imah Luluk Kusminah; Dianita Wardani; Lely Pramesty; Richo Oktavian Indarto (Universitas Islam Raden Rahmat, Malang, 2023)
As an archipelagic country, ship transportation is very important to connect between islands in Indonesia. In ship construction planning, ship hull material is an important factor because corrosion often occurs. Corrosion is the deterioration of a material due to a chemical reaction. This research is an interesting scientific discussion to find out cause the failure of ship hull materials. This research was conducted using an experimental method. Quantitatively the weight loss of aluminum material is calculated according to ASTM G31-72, then calculates the corrosion rate and analyzes the factors that affect the corrosion rate with XRD testing. From the results of the weight loss test, the largest corrosion rate occurred in the material located at 3.6% NaCl salinity conditions of 12.18 mpy with an immersion time of 1 month. From the results of XRD analysis showed that there were compounds 2NaAlO2 and Al2O3 at the highest peak intensity.